Neutron reflectivity of adsorbed water-soluble block copolymers at the air/water interface: The effects of composition and molecular weight - An, S; Thomas, R; Baines, F; Billingham, N; Armes, S; Penfold, J (1998)
We have used neutron reflection to follow the effects of composition and molecular weight on the structure of layers of poly(2-(dimethylamino)ethyl methacrylate-block-methyl methacrylate copolymer (poly(DMAEMA-b-MMA)) adsorbed at the air/water interface. We had previously shown that for a 70% DMAEMA copolymer of Mn about 10K at a pH of 7.5 there is a surface phase transition from a layer about 20 Å thick to one about 40 Å thick and that the adsorbed layer at the higher concentration has a layered cross-sectional structure with the most Hydrophobic part of the polymer forming a central layer rather than the outer layer in contact with air, as would be expected. The present work shows that copolymers containing 80% DMAEMA (about the same Mn) and 70% DMAEMA (Mn about 20K) form the same layered structure at the surface. The 80% DMAEMA copolymer is more surface active than the 70% copolymer, and this parallels the tendency to aggregate into micelles in bulk solution. The increase in molecular weight from 10K to 20K decreases the surface activity of the 70% DMAEMA copolymer. Addition of electrolyte enhances the formation of the layered structure at the interface but tends to equalize the surface activities of the three copolymers. Other surprising features are the increase of surface activity with increasing polyelectrolyte block size when the block is the larger component and the apparent suppression of ionization in the surface region.